Sensuous hermeneutics - Adam, A. K. M. 1957- (2019)
The single greatest impediment to clarity in hermeneutics arises from the intuition that words have meaning as a property. This essay will show an alternative to the hermeneutics of subsistent meaning, displaying a way to think about hermeneutics as an interplay of expression and apprehension. By learning about “meaning” from the more pervasive phenomenon of inference and apprehension and reasoning toward language as a special case — rather than beginning from language (which harbours subsistent “meaning”) and treating other patterns of apprehension as “the language of music,” “the language of flowers,” and so on — we can articulate a hermeneutic that better explains interpretive difference, and provides ways to evaluating interpretive claims outwith the customary bounds of exegetical correctness.
Keywords: Tansey Magritte; Comics theory